Malnutrition with hypoaminoacidemia in a 22-year-old pregnant patient masking a likely ornithine transcarbamylase deficiency. (April 2019) - Lefrère, B.; Ulmann, G.; Chartier, M.; Patkaï, J.; Cynober, L.; Neveux, N.
Summary: Background: Symptoms and clinical presentations of OTC deficiency vary widely according to the remaining activity of the enzyme. Three factors determine the residual enzyme activity. First, as the OTC gene is carried on the X chromosome, a complete inactivation of this enzyme in a newborn boy results an acute ammonia intoxication. Second, the female mosaicism due to lyonization (differential randomized X-inactivation) leads to differential OTC expression in hepatocytes. Third, the degree of severity depends on the mutation and the level of remaining activity it leaves to the protein. Published cases of OTC deficiency during pregnancy are scant. Most often, diagnosis of the metabolic disease is made before pregnancy or during the post-partum period. Methods: We report the case of a 22-year-old woman's successful pregnancy with a moderate form of ornithine transcarbamylase (OTC) deficiency, unsuspected before pregnancy, biochemically consistent with plasma aminoacidogram and orotic acid analysis, and initially masked by malnutrition. Results - conclusion: Although maternal ammonia was subnormal and the neonate was safe, an OTC deficiency was revealed by stress factors such as the pregnancy itself and infection, and associated with uncontrollable maternal vomiting and psychiatric syndrome. However, this metabolic disease, revealed by aminoacidogram and urine orotic acid analysis, fortunately did not prevent a successful pregnancy. Even if infrequent, this situation deserves to be highlighted.